EL COMPONENTE BETA DE LA DIVERSIDAD DE MAMÍFEROS DE MÉXICO - Rodríguez, Pilar; Soberón, Jorge; Arita, Héctor T. (Instituto de Ecología, A.C., 2003)
Beta diversity, or species turnover, is a poorly understood component of species richness. In the case of Mexico, empirical evidence shows that beta diversity is a more important determinant of regional diversity than the alpha or local component. Therefore, the unusual species richness of Mexico is more a consequence of a strong geographic species turnover rather than a particularly high local diversity. The hypothesis of Mexico as a beta- diverse country is based not only on indirect inferences but on data that have been accumulated in the scientific literature in the last few years. In this paper, we review that information and present new analyses that explore the contribution of species turnover to the building of the megadiversity of Mexican mammals. In an analysis using latitudinal bands, we found that the pattern of variation of beta diversity along a latitudinal gradient is similar for volant and non-volant mammals. However the patterns of diversity of terrestrial mammals are much more associated to beta diversity. In exploring beta diversity within biogeographic provinces defined with the distribution of mammals, we found that the relative contribution of alpha and beta diversity to the regional species richness varies geographically and is correlated with different environmental variables. We also present data showing the effect of heterogeneity on alpha and beta diversity, and show a direct relationship between beta diversity and the complementarity among sites in selecting priority areas for the conservation of biological diversity.